A Model for Classification Usability Testing Practically from the Agile Methodology Aspect - Salman, Fouad; Baluch, Bakhtawar; Bakar, Zuriana Abu (JOIV : International Journal on Informatics Visualization, 2025)
Usability is a crucial feature in the success of software products. Development practitioners know that to preserve and improve the quality of the product and usability has to be carefully considered throughout the development process. The tendency toward empowering users in software development drives the ongoing pursuit of solutions to reconcile agile and usability goals. In this paper, the authors aim to develop a model for classifying usability testing methods according to aspects of agile methodologies. This model can enable agile practitioners to obtain end-user feedback when implementing usability tests at the appropriate time and place during development and thus produce useful and usable software. Mixed methods (qualitative and quantitative) were used in this research to collect primary and secondary data. This research adopted the convenience non-probability sampling technique for evaluating the model.  The evaluation determines whether it could provide valuable information supporting consistent usability tests. The method of performance profiles is also applied in this evaluation to gain accurate results and avoid any biases that might unnecessarily affect the outcomes. The evaluation results were encouraging, and the model showed beneficial effects in integrating usability work into an agile approach, especially since all attributes showed high importance among participants' accepted satisfaction, representing the least essential scale. The developed model must be applied practically to the other integration models in future work. Furthermore, several observation techniques are required to thoroughly cover the integration by software development teams from diverse organizations.